Teachers’ efforts to increase students’ confidence in speaking Indonesian in Sarolangun through language habituation - Nugraheni, Aninditya Sri; Abroto, (Frontiers in Education, 2022)
This research is aimed at investigating teachers’ habituation pattern as an effort to enhance students’ confidence in speaking Indonesian language in Sarolangun. It implements qualitative phenomenology approach to understand why and how an incident takes place. The data are collected through observation, interview, and documentation. The subjects of the research are Indonesian students and teachers from three different senior high schools in Sarolangun, Indonesia. The results reveal that students are low skilled in using Indonesian language, and they have low confidence in speaking in Indonesian due to bullying. The senior high school teachers in Sarolangun try to improve the students’ confidence in speaking Indonesian through encouragement, punishment for the bullies, and compulsory program to use Indonesian at school. These are considered as a proper policy in boosting students’ confidence. This research concludes that in the teaching of Indonesian, the language should not be used by a certain group of people but rather it could be used by all people regardless of their social class. Furthermore, Indonesian is the language used in academic and official context. Indonesia, indeed, constitutes of various tribes and languages. The aim of Indonesian language usage is to ease people from many different ethnicities and regions to communicate to each other.